The Practically Level of Students’ Worksheets on Parabolic Materials Based on Guided Discovery - Iltavia Iltavia; Yurnalis Yurnalis; Fathur Rahmi (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2022)
The global Covid-19 pandemic has resulted in a change in the way people learn. Face-to-face learning is transformed into daring learning with the use of the internet network. One option that is facilitated by learning and that may be learned at any moment is presented. The researcher created a student worksheet that students would evaluate to see how practical it was. The Mc Kenny development research model is used in this study. The participants in this study were third-semester Mathematics Education Study Program students from IAIN Bukittinggi. After using the designed teaching materials, two experts and students evaluated the product's practicality. The results showed that the instructional materials provided met the practical criteria with a percentage of 79.17 based on the evaluation of two experts and 83 percent based on a student questionnaire. The study's result is that the generated teaching materials have been deemed useful by both experts and students.